Characteristics of Musical Ability Development (Texas Journal of Multidisciplinary Studies, 2022)
Music lessons are specific forms of manifestation of mental activity of the child's personality. The development of more musical hearing of students through musical abilities. The process of performing music lessons in secondary schools is one of the most important tasks